2020
DOI: 10.1177/0093854819898219
|View full text |Cite
|
Sign up to set email alerts
|

Drug Testing and Community Supervision Outcomes

Abstract: The requirement to submit to drug testing is either a standard or special condition of adult community correctional supervision in most jurisdictions. Positive drug test results are one of the most common violations of probation that result in official action by a supervising officer. This study examines the relationship between individual characteristics, drug test results, and federal supervision outcomes. Results indicate that individual risk score and offense category are associated with positive drug test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, when POs were trained in both STARR and motivational interviewing, failure rates for high-risk probationers were reduced (Lowenkamp et al, 2014). In a recent study of STARR, Hicks and colleagues (2020) found decreased revocations for new crimes or non-drug-related technical violations among clients supervised by trained officers, but increased revocations for positive drug tests. Chadwick and colleagues (2015) conducted a meta-analysis of the existing literature on officer training programmes, suggesting training resulted in a 14% reduction in recidivism.…”
Section: Community Supervision Officer Training Programmesmentioning
confidence: 99%
“…However, when POs were trained in both STARR and motivational interviewing, failure rates for high-risk probationers were reduced (Lowenkamp et al, 2014). In a recent study of STARR, Hicks and colleagues (2020) found decreased revocations for new crimes or non-drug-related technical violations among clients supervised by trained officers, but increased revocations for positive drug tests. Chadwick and colleagues (2015) conducted a meta-analysis of the existing literature on officer training programmes, suggesting training resulted in a 14% reduction in recidivism.…”
Section: Community Supervision Officer Training Programmesmentioning
confidence: 99%
“…19 Further, research to date has established that alcohol and illicit substance use are inversely associated with the completion of a community corrections sentence. 19,20 The failure to successfully complete a community corrections sentence leads to further sanctions and possible incarceration. 2 Furthermore, alcohol use, illicit substance use, and substance use disorders are strongly linked with recidivism.…”
Section: Substance Use Behaviors Among Adults On Community Correctionsmentioning
confidence: 99%
“…Despite the posttraining increases noted in the use of these correctional skills, there remains significant room for improvement as trained officers appear to only apply the CCPs in 28% to 58% of their one-on-one interactions with clients (Bonta et al, 2011;Latessa et al, 2013;Robinson et al, 2011;Viglione & Labrecque, in press). These studies have also revealed that even when some trained officers apply these skills in practice, they often fail to do so with fidelity (Hicks et al, 2020;Labrecque et al, 2013;Latessa et al, 2013).…”
Section: Research On Community Supervision Officer Training Programsmentioning
confidence: 99%
“…Another investigation reported that clients supervised by officers who displayed high-fidelity to the EPICS skills were less likely to be re-incarcerated or arrested for a new offense but were more likely to have received a technical violation than those monitored by low-fidelity officers (Latessa et al, 2013). Similarly, clients supervised by officers who were rated as proficient in the STARR model were less likely to have their probation revoked for a new crime or nondrug-related technical violation but were more likely to be revoked for positive drug test (Hicks et al, 2020).…”
Section: Research On Community Supervision Officer Training Programsmentioning
confidence: 99%
See 1 more Smart Citation